Nasosinusal Endoscopic Anatomy and Physiology - Simoncello, Lívia Miotta; Antonio, Gabriel Farias; Pereira, Barbara Casalecchi; Portela Júnior, Estevan Martin; Silva, Marcelo Nery (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
The present article focuses on the analysis of the nasal cavity's anatomy succinctly and descriptively. This essay was carried out through a bibliographic review, directed to the detailed anatomy of the nasal cavity, and the structures that form its sinuses. We have identified the need for more studies directed to the related anatomical area so that the improved knowledge of this region ensures a nasoendoscopic treatment with better effectiveness and no complications.
Keywords: anatomy; nasal cavity; nasoendoscopy; neurosurgery